PELATIHAN CODING FOR TEENS DAN DIGITAL CONTENT CREATION SEBAGAI PENINGKATAN LITERASI DIGITAL DI DESA NGASEM - Saraswati, Galuh Wilujeng; Lutfina, Erba (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The high rate of juvenile delinquency and school dropouts in Ngasem Village, Ngasem District, Kediri Regency, has become an urgent social issue that must be addressed. This problem is exacerbated by the lack of digital literacy and the absence of non-formal learning activities for village youth. This community service program aims to enhance digital literacy through Coding for Teens and Digital Content Creation training as a preventive measure against juvenile delinquency. The implementation method uses the ABCD (Asset-Based Community Development) approach, consisting of appreciative interviews, community asset mapping, asset mobilization, action plan formulation, and monitoring and evaluation. The results of the program show the successful development of an applicable non-formal curriculum and high participant enthusiasm. Based on the satisfaction survey, 60% of participants were satisfied and 40% were very satisfied with the training. Regarding expectation alignment, 72% of participants were very satisfied, 20% were satisfied, and 8% considered it adequate. As for the responsiveness of the team to participant questions, 68% felt very satisfied and 32% were satisfied. Moreover, 60% of participants recommended follow-up training. These outcomes indicate that the training succeeded in fostering digital learning interest, forming youth-led task forces, and creating a renewed spirit in utilizing technology for positive and productive purposes. It is expected that this program can be continued and become a model for digital literacy-based community empowerment in other rural areas.